Cardiac T1 and T2 Mapping Showed Myocardial Involvement in Recovered COVID‐19 Patients Initially Considered Devoid of Cardiac Damage. Issue 2 (16th February 2021) - Pan, Cunxue; Zhang, Zuoquan; Luo, Liyun; Wu, Wenhao; Jia, Taoyu; Lu, Ling; Liu, Weiyin V.; Qin, Yujuan; Hu, Feng; Ding, Xianglian; Qin, Peixin; Qian, Long; et al.
Abstract : Background: Myocardial injury has been found using magnetic resonance imaging in recovered coronavirus disease 2019 (COVID‐19) patients unselected or with ongoing cardiac symptoms. Purpose: To evaluate for the presence of myocardial involvement in recovered COVID‐19 patients without cardiovascular symptoms and abnormal serologic markers during hospitalization. Study Type: Prospective. Population: Twenty‐one recovered COVID‐19 patients and 20 healthy controls (HC). Field Strength/Sequence: 3.0 T, cine, T2‐weighted imaging, T1 mapping, and T2 mapping. Assessment: Cardiac ventricular function includes end‐diastolic volume, end‐systolic volume, stroke volume, cardiac output, left ventricle (LV) mass, and ejection fraction (EF) of LV and right ventricle (RV), and segmental myocardial T1 and T2 values were measured. Statistical Tests: Student's t ‐test, univariate general linear model test, and chi‐square test were used for analyses between two groups. Ordinary one‐way analyses of variance or Kruskal–Wallis H test were used for analyses between three groups, followed by post‐hoc analyses. Results: Fifteen (71.43%) COVID‐19 patients had abnormal magnetic resonance findings, including raised myocardial native T1 (5, 23.81%) and T2 values (10, 47.62%), decreased LVEF (1, 4.76%), and RVEF (2, 9.52%). The segmental myocardial T2 value of COVID‐19 patients (49.20 [46.1, 54.6] msec) was significantly higher than HC (48.3 [45.2, 51.7] msec) ( P <  0.001), while the myocardial native T1 value showed no significant difference between COVID‐19 patients and HC. The myocardial T2 value of serious COVID‐19 patients (52.5 [48.1, 57.1] msec) was significantly higher than unserious COVID‐19 patients (48.8 [45.9, 53.8] msec) and HC (48.3 [45.2, 51.7]) ( P <  0.001). COVID‐19 patients with abnormally elevated D‐dimer, C‐reactive protein, or lymphopenia showed higher myocardial T2 values than without (all P <  0.05). Data Conclusion: Cardiac involvement was observed in recovered COVID‐19 patients with no preexisting cardiovascular disease, no cardiovascular symptoms, and elevated serologic markers of myocardial injury during the whole course of COVID‐19. Level of Evidence: 1 Technical Efficacy: Stage 5